Catch‐and‐Release Probes Applied to Semi‐Intact Cells Reveal Ubiquitin‐Specific Protease Expression in Chlamydia trachomatis Infection. Issue 3 (18th January 2013) - Claessen, Jasper H. L.; Witte, Martin D.; Yoder, Nicholas C.; Zhu, Angela Y.; Spooner, Eric; Ploegh, Hidde L.
Abstract Protein ubiquitylation controls many cellular pathways, and timely removal of ubiquitin by deubiquitylating enzymes (DUBs) is essential to govern these different functions. To map endogenous expression of individual DUBs as well as that of any interacting proteins, we developed a catch‐and‐release ubiquitin probe. Ubiquitin was equipped with an activity‐based warhead and a cleavable linker attached to a biotin affinity‐handle through tandem site‐specific modification, in which we combined intein chemistry with sortase‐mediated ligation. The resulting probe is cell‐impermeable and was therefore delivered to the cytosol of perfringolysin O (PFO)‐permeabilized cells. This allowed us to retrieve and identify 34 DUBs and their interacting partners. We also noted the expression, in host cells infected with Chlamydia trachomatis, of two additional DUBs. Furthermore, we retrieved and identified chlamydial DUB1 (ChlaDUB1) and DUB2 (ChlaDUB2), demonstrating by experiment that ChlaDUB2, the presence and activity of which had not been detected in infected cells, is in fact expressed during the course of infection.